An algorithm for computing the critical state of unilateral buckling of thin plates - Ayadi, Mekki (European Journal of Computational Mechanics, 2006)
When modelling the buckling phenomenon of thin plates in presence of an obstacle, we obtain a variational inequality with two unknowns that are the buckling load and the corresponding buckling mode. Using the finite elements method, the continuous problem is approximated by a discrete problem. Then, an algorithm for computing the buckling critical load and the corresponding unilateral buckling mode of the plate is suggested. The last part of the paper is devoted to some numerical results obtained for the same rectangular plate but three different kinds of obstacle.